Musculoskeletal disorders in support workers in the aged care sector. (June 2013) - Chang, Victor; Hiller, Christina; Keast, Emma; Nicholas, Paul; Su, Marie; Hale, Leigh
Abstract : Background: With the proportion of the population aged over 65 expecting to rise from 15 to 26% within the next 50 years, the demand for formal support workers for older adults will rise substantially. It is essential that this workforce remain healthy; however, due to the nature of elder care, musculoskeletal complaints are commonplace in support workers. Objectives: The aim of this systematic review was to determine the current work-related musculoskeletal disorders which are present in workers in the aged care sector. Method: Five databases were searched: AMED, CINAHL, EMBASE, Medline, and Web of Science. Four main concepts: aged care, physical health, carer/support worker, and work, were included in the search. All study design types where participants were involved in the formal care of the older adults were included. Results: The search yielded 17 articles after the implementation of strict inclusion and exclusion criteria. Common musculoskeletal complaints included neck, shoulder, and back pain with a prevalence ranging between 5 and 51%. Associated risk factors for injury included: high physical job demands, psychosocial factors, effort-reward imbalance, lack of career opportunities, increased age, and decreased education levels. Conclusion: Current evidence shows that the back, neck, and shoulder are the main musculoskeletal complaints of workers in the aged care sector. However specific diagnoses of these injuries have not been investigated. Further research should focus on quantifying specific disorders, determining risk factors, and developing prevention strategies.